Serial burn [large type] - Eason, Lynette (Eason, Lynette. Lake City heroes, 2025)
"Now the fire marshal of Lake City, Jesslyn McCormick is determined to find the person who started the fire that robbed her of her family when she was just seven years old. As the twentieth anniversary of the tragedy approaches, a string of fires offers new evidence. FBI Special Agent Nathan Carlisle is called in to work with local law enforcement. Nathan has his own past he'd prefer not to revisit, and helping Jesslyn track down the arsonist is a great distraction. When Jesslyn comes face-to-face with her worst nightmare, she'll have to confront her fears and rely on Nathan and her community of friends in order to survive."--from back cover.